TEENAGERS’ PERCEPTION OF TRADITIONAL SNACKS : CASE STUDY IN SURABAYA AND SIDOARJO - Alvin Maulidiah; Mubarokah Mubarokah; Mirza Andrian Syah (Journal of Management Small and Medium Enterprises (SMEs), 2025)
There are many culinary phenomena, such as street food stalls that sell modern cuisine, making the existence of traditional cuisine heavy. Traditional culinary also consists of traditional snacks. Various age groups can consume traditional snacks, but it has been found that teenagers are more inclined to consume modern foods. This study aims to analyze the perception of teenagers in Surabaya and Sidoarjo towards traditional snacks. The research locations were carried out in Surabaya and Sidoarjo. The method used in this research is the descriptive analysis method with likert scale measurement, which is used to measure attitudes, opinions, and perceptions. The study's results indicate that the overall perception of teenagers in Surabaya and Sidoarjo towards traditional snacks, evaluated across four aspects : quality, food safety, price, and culture, were found in the good category. Keywords: Perception; Teenager; Traditional Snack